Interferons block protein kinase C-dependent but not-independent activation of Raf-1 and mitogen-activated protein kinases and mitogenesis in NIH 3T3 cells. - Xu, J (1994)
Interferons (IFNs) exert antiproliferative effects on many types of cells. The underlying molecular mechanism, however, is unclear. One possibility is that IFNs block growth factor-induced mitogenic signaling, which involves activation of Ras/Raf-1/MEK/mitogen-activated protein kinase. We have tested this hypothesis by using HER14 cells (NIH 3T3 cell expressing both platelet-derived growth factor [PDGF] and epidermal growth factor [EGF] receptors) as a model system. Our studies showed that IFNs (alpha/beta and gamma) blocked PDGF-and phorbol ester- but not EGF-stimulated DNA synthesis and cell proliferation. While the ligand-stimulated receptor tyrosine phosphorylation and interaction with downstream signaling molecules, such as GRB2, were not affected, IFNs specifically blocked PDGF- and phorbol ester- but not EGF-stimulated activation of Raf-1, mitogen-activated protein kinases, and tyrosine phosphorylation of an unidentified 34-kDa protein. This inhibition could be detected as early as 5 min after IFN treatments and was insensitive to cycloheximide, indicating that de novo protein synthesis is not required. The IFN-induced inhibition acted upstream of Raf-1 kinase and downstream of diacyl glycerol/phorbol ester, suggesting that protein kinase C (PKC) is the potential primary target. Consistently, downregulation of PKC by chronic phorbol myristate acetate treatment or inhibition of PKC by H7 and staurosporine blocked PDGF- and phorbol myristate acetate- but not EGF-induced signaling and DNA synthesis. Moreover, incubating cells with antisense oligodeoxyribonucleotides of PKC delta eliminated production of PKC delta protein and specifically blocked PDGF- but not EGF-stimulated mitogenesis in these cells. Thus, these studies have elucidated a major difference in the early events of EGF-and PDGF-stimulated signal transduction and, more importantly, revealed a novel mechanism by which IFNs may execute their antiproliferative function.